Religious Pluralism and Religion-State Relations in Turkey - ALBAYRAK, HAFİZE ŞULE (MDPI, 2019)
In this article, I examine religion-state relations and religious pluralism in Turkey in terms of recent changes in the religious landscape. I propose that there is a growing trend in the religious sphere that has resulted in a proliferation of religions, sects and spiritual approaches in Turkey. I argue that although the religious market model might not be applicable to the Turkish religious sphere during the republican era until the 2000s due to the restrictions applied by the state's authoritarian secularist policies, it is compatible with today's changing society. Different religious groups as well as spiritual movements have used the democratization process of the 2000s in Turkey as an opportunity to proselytize various faiths and understandings of Islam, with both traditional and modernist forms. In this period, new religious movements have also appeared. Thus, the Turkish religious landscape has recently become much more complicated than it was two decades earlier. I plan for this descriptive work firstly to provide an insight into the history of religious pluralism and state policies in Turkey. Secondly, I will discuss the religious policies of the republican period and, thirdly, I will evaluate recent developments such as the increasing number of approaches in the religious sphere within the scope of the religious market model.
Keywords: Turkey; religious pluralism; secularism; Islam; religious market; laicism; ISLAM